To find the product of the polynomials \( (2x + 1)(x + 4) \), we can use the distributive property (also known as the FOIL method for two binomials).
-
Multiply the first terms: \[ 2x \cdot x = 2x^2 \]
-
Multiply the outer terms: \[ 2x \cdot 4 = 8x \]
-
Multiply the inner terms: \[ 1 \cdot x = 1x \]
-
Multiply the last terms: \[ 1 \cdot 4 = 4 \]
Now, we combine all these results: \[ 2x^2 + 8x + 1x + 4 = 2x^2 + (8x + 1x) + 4 \] \[ = 2x^2 + 9x + 4 \]
Thus, the product of the polynomials \( (2x + 1)(x + 4) \) is: \[ \boxed{2x^2 + 9x + 4} \]